2012
DOI: 10.1248/bpb.b12-00022
|View full text |Cite
|
Sign up to set email alerts
|

Water Extracts of Immature <i>Rubus coreanus</i> Regulate Lipid Metabolism in Liver Cells

Abstract: Hyperlipidemia is a major contributor for atherosclerosis and hypolipidemic drugs such as statin are highly prescribed to treat elevated lipid level in plasma. Rubus coreanus, which is widely cultivated in south eastern Asia, have been reported to show significant cholesterol lowering action in hyperlipidemic subjects. Our objective was to determine the cellular effect of Rubus coreanus extract (RCE) on cholesterol biosynthesis in human hepatic cells (HepG2) and to elucidate the molecular mechanism by which it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…[293031] The plants grow in Far East Asian countries, namely South Korea, Japan, and China. [32] The anthocyanin fraction of black raspberry has been found to be protective against esophageal and colorectal cancer. [31] Montrose and coworkers investigated the protective effects of freeze-dried black raspberry powder on dextran sodium sulfate (DSS)–induced UC in C57BL/6J mice and observed it to be effective in ameliorating the clinical conditions.…”
Section: Dietary Agents With Anti-ibd Effectsmentioning
confidence: 99%
“…[293031] The plants grow in Far East Asian countries, namely South Korea, Japan, and China. [32] The anthocyanin fraction of black raspberry has been found to be protective against esophageal and colorectal cancer. [31] Montrose and coworkers investigated the protective effects of freeze-dried black raspberry powder on dextran sodium sulfate (DSS)–induced UC in C57BL/6J mice and observed it to be effective in ameliorating the clinical conditions.…”
Section: Dietary Agents With Anti-ibd Effectsmentioning
confidence: 99%
“…It has been used for nourishment and as traditional remedies, especially in the immature form, in Asian countries [6,8]. Numerous studies have reported that the active compounds present in this fruit include various antioxidants, such as flavonoids and organic acids, and have investigated its significant antitumor, anti-inflammatory, and lipid metabolism effects [9,10,11]. However, for commercial use, the quality of RO needs to be enhanced and this process has been achieved by using the black raspberry crop harvested from Gochang, Korea, the largest producer of black raspberry in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of studies, various factors such as the sampling period or extraction conditions were optimized to produce fruits with a high content of bioactive principles [12,13]. In fact, the effects of Rubus coreanus on individual symptoms, such as its antiobesity or cholesterol-lowering effects, have previously been identified [11,14,15], while other species, especially RO, are rarely studied regarding metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…After characterizing the chemical compounds extracted from the leaves, we investigated whether the extracts exhibited antidiabetic properties in an alloxan-induced diabetes rat model. [1,4,7,8,10,[14][15][16]…”
Section: Introductionmentioning
confidence: 99%